DNA synthesis generally initiates outside the simian virus 40 core origin in vitro. - Bullock, P A (1995)
The nucleotide positions at which DNA synthesis initiates in vitro, in the vicinity of the simian virus 40 origin, have been determined. Start sites for DNA synthesis are greatly suppressed over the simian virus 40 core origin. Relatively weak start sites are detected over the 21-bp repeats and T-antigen-binding site I; distal to these regions, stronger start sites are detected. Thus, studies using a model system for eukaryotic DNA replication indicate that DNA synthesis events initiate, in general, outside the core origin.